Rethinking the concept of 'healing settlements' : water, cults, constructions and contexts in the ancient world : Roman Archareology Conference 2016 : proceedings of the Session of Study (nr. 27), Sapienza University, Aula 'Partenone', 17th March 2016 - Bassani, Maddalena,; Bolder-Boos, Marion,; Fusco, Ugo, 1970- (Archaeopress Roman archaeology ;, 2019)
This volume brings together papers dealing with therapeutic aspects connected to thermo-mineral sites both in Italy and in the Roman Provinces, as well as cultic issues surrounding health and healing.